Holocene climate forcings and lacustrine regime shifts in the Indian summer monsoon realm. Issue 15 (1st October 2020) - Prasad, Sushma; Marwan, Norbert; Eroglu, Deniz; Goswami, Bedartha; Mishra, Praveen K.; Gaye, Birgit; Anoop, A.; Basavaiah, N.; Stebich, Martina; Jehangir, Arshid
Abstract: Extreme climate events have been identified both in meteorological and long‐term proxy records from the Indian summer monsoon (ISM) realm. However, the potential of palaeoclimate data for understanding mechanisms triggering climate extremes over long time scales has not been fully exploited. A distinction between proxies indicating climate change, environment, and ecosystem shift is crucial for enabling a comparison with forcing mechanisms (e.g. El‐Niño Southern Oscillation). In this study we decouple these factors using data analysis techniques [multiplex recurrence network (MRN) and principal component analyses (PCA)] on multiproxy data from two lakes located in different climate regions – Lonar Lake (ISM dominated) and the high‐altitude Tso Moriri Lake (ISM and westerlies influenced). Our results indicate that (i) MRN analysis, an indicator of changing environmental conditions, is associated with droughts in regions with a single climate driver but provides ambiguous results in regions with multiple climate/environmental drivers; (ii) the lacustrine ecosystem was 'less sensitive' to forcings during the early Holocene wetter periods; (iii) archives in climate zones with a single climate driver were most sensitive to regime shifts; (iv) data analyses are successful in identifying the timing of onset of climate change, and distinguishing between extrinsic and intrinsic (lacustrine) regime shifts by comparison with forcing mechanisms. Our results enable development of conceptual models to explain links between forcings and regional climate change that can be tested in climate models to provide an improved understanding of the ISM dynamics and their impact on ecosystems. © 2020 John Wiley & Sons, Ltd. Abstract : Statistical analyses of multiproxy Holocene data from the Lonar and Tso Moriri lakes in the Indian summer monsoon (ISM) realm are used to understand climate forcings triggering (extreme) climate events and identify ecosystem response.